Spatial Analysis for Enhancing the Use of Health Data Availability from Different Sources to Help the Decision-Making Process - Eryando, Tris (UI Scholars Hub, 2022)
Spatial analysis in public health has become a common method used by researchers to understand the distribution of public health aspects related to the surrounding environment. It can also be used to analyze individual information in the form of a dot and the location or line of aggregated information in a specific area of study. Another benefit is the possibility of using different data sources to be analyzed in one statistical model analysis, as long as the identification area is sufficiently clear as a key variable. Spatial analysis can show an object's distribution on a locational map and explain the distribution type, whether random, cluster, or uniform. The statistical analysis model can also develop different risk factors for each region of the research area. A specific model sometimes explains how to treat health issues differently in a specific location and can be used as an alternative approach to dealing with an intervention plan for public health issues based on specific local phenomena.